The Effects of Profitabilitas and Activity Ratio Toward Firms Value With Stock Price as Intervening Variables - I Gusti Ngurah Bagus Gunadi; I Gede Cahyadi Putra; Ida Ayu Nyoman Yuliastuti (AIBPM Publisher, 2020)
The purpose of this paper is to discuss the effect profitability ratios and activities on firms’ value with stock prices as intervening variable. The study was conducted for 10 years on 39 property, real estate and building construction companies listed on the Indonesia Stock Exchange. The results showed profitability and activity had a positive effect on stock prices, but did not affect the value of the company. Stock prices are able to mediate the effect of profitability and activity on firm value. The research implications show that the higher profitability and activity ratios cause stock prices to rise and result in an increase in the value of the company.